Positive and Negative Regulatory Roles of C-Terminal Src Kinase (CSK) in FcεRI-Mediated Mast Cell Activation, Independent of the Transmembrane Adaptor PAG/CSK-Binding Protein - Potuckova, Lucie; Draberova, Lubica; Halova, Ivana; Paulenda, Tomas; Draber, Petr (Frontiers in Immunology, 2018)
C-terminal Src kinase (CSK) is a major negative regulator of Src family tyrosine kinases (SFKs) that play critical roles in immunoreceptor signaling. CSK is brought in contiguity to the plasma membrane-bound SFKs via binding to transmembrane adaptor PAG. The recent finding that PAG can function as a positive regulator of the high-affinity IgE receptor (FcεRI)-mediated mast cell signaling suggested that PAG and CSK have some non-overlapping regulatory functions in mast cell activation. To determine the regulatory roles of CSK in FcεRI signaling, we derived bone marrow mast cell (BMMCs) with reduced or enhanced expression of CSK from wild-type or PAG knockout (KO) mice and analyzed their FcεRI-mediated activation events. We found that in contrast to PAG-KO cells, antigen-activated BMMCs with CSK knockdown (KD) exhibited significantly higher degranulation, calcium response, and tyrosine phosphorylation of FcεRI, SYK, and phospholipase C. Interestingly, FcεRI-mediated events in BMMCs with PAG-KO were restored upon CSK silencing. BMMCs with CSK-KD/PAG-KO resembled BMMCs with CSK-KD alone. Unexpectedly, cells with CSK-KD showed reduced kinase activity of LYN and decreased phosphorylation of transcription factor STAT5. This was accompanied by impaired production of proinflammatory cytokines and chemokines in antigen-activated cells. In line with this, BMMCs with CSK-KD exhibited enhanced phosphorylation of protein phosphatase SHP-1, which provides a negative feedback loop for regulating phosphorylation of STAT5 and LYN kinase activity. Altogether, our data demonstrate a novel CSK-dependent regulatory mechanism in FcεRI-activated mast cells, which drives proinflammatory cytokine and chemokine production through the LYN/SHP-1/STAT5 axis.